2013
DOI: 10.1080/15374416.2013.814539
|View full text |Cite
|
Sign up to set email alerts
|

Callous-Unemotional Traits and Anxiety in a Community Sample of 7-Year-Olds

Abstract: In forensic samples of adults and adolescents, there is evidence to suggest that there may be distinct variants of psychopathy marked by the presence/absence of significant levels of anxiety. Callous-unemotional (CU) traits can be used to characterize children who share behavioural and neurocognitive features with adult psychopaths. The aims of this paper are to (a) investigate the genetic and environmental influences on CU traits with/without anxiety and (b) explore differences in terms of concurrent and earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 44 publications
2
29
1
Order By: Relevance
“…One such study used items from the Antisocial Process Screening Device (APSD) (Frick and Hare 2001) and Strengths & Difficulties Questionnaire (SDQ) (Goodman 1997) to assess the heritability of CU traits in 7-year-old twins with elevated CU traits (i.e., > 1.3 SD above the mean). This study found a heritability of approximately 75% (Humayun et al 2014). Similar studies using selected samples have also found childhood heritabilities for high levels of CU traits in the range of 80% (e.g., Viding et al 2005; Viding et al 2008), although these results are not generalizable to a community sample of children due to their reliance on the upper end of the CU trait distribution.…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…One such study used items from the Antisocial Process Screening Device (APSD) (Frick and Hare 2001) and Strengths & Difficulties Questionnaire (SDQ) (Goodman 1997) to assess the heritability of CU traits in 7-year-old twins with elevated CU traits (i.e., > 1.3 SD above the mean). This study found a heritability of approximately 75% (Humayun et al 2014). Similar studies using selected samples have also found childhood heritabilities for high levels of CU traits in the range of 80% (e.g., Viding et al 2005; Viding et al 2008), although these results are not generalizable to a community sample of children due to their reliance on the upper end of the CU trait distribution.…”
Section: Introductionmentioning
confidence: 50%
“…At visit 1 an AE model fit the data best, indicating 39% of the variance in parent-report ICU was due to the latent genetic factor A, with the remaining 61% variance due to the unique environmental factor E. The heritability for visit 1 of the current study appears lower than some previously reported estimates. Earlier twin studies of CU traits reported heritability estimates ranging from 40–79% (Bezdjian et al 2011; Viding and McCrory 2012; Humayun et al 2014; Mann et al 2015; Henry et al 2016). However, the highest estimates stem from studies that examined the heritability of specific ICU factors (Henry et al 2016) or focused on individuals with extreme CU traits (Humayun et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results derived from observational child aggression data are consistent with previous research that has only utilized questionnaire-based data on child aggression (e.g., Fanti et al, 2013;Humayun et al, 2013;Rosan et al, 2015) in suggesting that CU traits are associated with greater aggression in the presence of higher levels of anxiety, and further clarify specific conditions under which this relationship applies. Specifically, the present findings obtained with an experimental paradigm indicate that anxiety moderates the effect of CU on child aggression, but only in the absence of salient distress cues from a potential victim.…”
Section: Overviewsupporting
confidence: 78%
“…It is worthwhile to assess the degree to which the aggressive reactivity and internalizing symptoms (e.g., Docherty et al, 2015;Fanti et al, 2013) reported by CU youth experiencing anxiety symptoms may actually represent traumatic stress symptoms. Thus far, trauma exposure and traumatic stress symptoms have been examined as clinical correlates differentiating variants of CU youth with respect to anxiety (e.g., Humayun et al, 2013;Kimonis et al, 2012); the potential for traumatic stress to moderate the link between CU and observed aggression in the context of experimentally manipulated distress cues has not been explored.…”
Section: Cu and Anxietymentioning
confidence: 99%